Choroidal findings in idiopathic uveal effusion syndrome - Harada T (Dove Medical Press, 2011)
Tomomi Harada, Shigeki Machida, Takamistu Fujiwara, Yasunori Nishida, Dajiro KurosakaDepartment of Ophthalmology, Iwate Medical University School of Medicine, Iwate, JapanPurpose: We report choroidal findings by means of enhanced depth imaging spectral-domain optical coherence tomography (EDI-OCT) in a patient with idiopathic uveal effusion syndrome (IUES).Case report: A 41-year-old man was referred to us with ciliochoroidal and non-rhegmatogenous retinal detachments. Sclerectomies and sclerostomies were performed at the equator in the lower quadrants, resulting in resolution of the ciliochoroidal and retinal detachments. EDI-OCT demonstrated low-reflective areas in the outer choroid. The subfoveal choroidal thickness measured vertically from the outer border of the RPE to the inner border of the sclera was 787 µm which was significantly thicker than the normal value (272 ± 90 µm, n = 131) obtained from age-matched normal controls.Conclusions: The findings made by EDI-OCT have provided additional evidence that choroidal alterations play a role in the pathological process in IUES.Keywords: uveal effusion syndrome, spectral-domain optical coherence tomography, EDI-OCT, OCT, choroid